Women's Double Burden in the Family Between Culture and Discrimination - Aziz, Muhammad (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This study endeavors to explore the multifaceted nature of women's double burden within the family framework, delving into the intersection of cultural norms, discriminatory practices, and gender perspectives that contribute to gender injustice. Employing a library research methodology encompassing books, articles, journals, news, and papers, this research adopts descriptive-analytical methods coupled with gender-focused approaches. The findings underscore a prevalent societal phenomenon where one gender shoulders a disproportionately heavier workload compared to the other, leading to a situation of double burden. Despite contemporary perceptions normalizing women's participation in the workforce, cultural constraints persist, perpetuating the dual responsibilities borne by women and perpetuating gender injustice. For women unencumbered by stringent cultural norms, barriers to employment persist due to various factors such as economic constraints and limited educational opportunities. To alleviate discrimination and mitigate double burden within households, several strategies emerge. First, dispelling the notion that work is solely a male domain is crucial. Second, fostering mutual agreements between spouses in distributing daily responsibilities can mitigate discrimination and uphold equitable commitments. Additionally, the establishment of women's advocacy groups in both rural and urban settings is pivotal. Social campaigns emphasizing equality play a vital role in eradicating injustice. Enforcing stringent penalties for offenders coupled with preventive measures aims to raise awareness among potential perpetrators. Ultimately, addressing women's double burden necessitates societal efforts to eliminate discrimination, fostering household harmony, and nurturing prosperity. Embracing gender equality and redefining societal roles are imperative steps toward realizing a fairer, more equitable future within familial settings.